The Effects of Using Ground Cockle Seashells as an Additive for Mortar in Peat Environment - Monita Olivia; Ismi Siska Rahmayani; Gunawan Wibisono; Edy Saputra (Journal of the Civil Engineering Forum, 2020)
Seashells are available abundantly in coastal areas and have the potential to be used as aggregates and replacement for cement in mortar and concrete. They are also applied as mineral additives for mortar or concrete to increase the resistance of these materials in an aggressive environment, especially in constructing structures such as drainage and sewer networks which require good resistance to organic acid attack. This paper discusses the potential addition of ground seashells to improve the performance of mortar used as a drainage lining in an acidic environment such as peatland. The mix was designed using a 4% ground cockle shell (Anadara granosa) by cement weight as an additive in two mixes which include Ordinary Portland Cement (OPC) and OPC Cockle Shell (OPCCS). The samples were cured in a water pond for 28 days before they were placed in water and peat water for 120 days after which the compressive strength, porosity, sorptivity, change in weight, and visual characteristics were investigated. The results showed the compressive strength of OPCCS mortar increased by 11.29% after immersion in peat water for 120 days with its porosity and sorptivity decreased by 5.78% and 31.07% due to the refinement of the pores and capillary network in the mortar. Moreover, the weight of the brushed and unbrushed OPCCS mortar in peat water was lesser compared to the OPC due to the increase in CaO content which has the ability to fill the pores and reduce disintegration. The visual examination showed an improvement in the pH of OPCCS mortar due to the ability of the ground cockle shells to neutralize the acidity of the peat water. This study, therefore, shows the use of ground cockle shells as an additive makes it possible to use mortar as a drainage lining because the shells provide excellent resistance to acidic peat environments.